Without Systems and Complexity Thinking There Is no Progress - or Why Bureaucracy Needs to Become Curious; Comment on "What Can Policy-Makers Get out of Systems Thinking? Policy Partners' Experiences of a Systems-Focused Research Collaboration in Preventive Health" - Joachim P. Sturmberg (Kerman University of Medical Sciences, 2021)
The bureaucracy's goal is to maintain uniformity and control within discrete areas of activity and relies on hierarchical processes and procedural correctness as means to suppress autonomous decision making. That worldview, however, is unsuited for problem solving of real world VUCA (Volatility, uncertainty, complexity and ambiguity) problems. Solving wicked problems in the VUCA world requires curiosity, creativity and collaboration, and a willingness to deeply engage and an ability to painstakingly work through their seemingly contradictory and chaotic pathways. In addition, it necessitates leadership. Leaders require a deep - indeed academic - understanding of the nature of the problems and the veracity of various problem-solving approaches. Leadership after all means "[facilitating] the necessary adaptive work that needs to be done by the people connected to the problem." That are the people at the coalface who understand and have to manage the complexities relating to problems unique to their local environment for which of the shelf solutions never work. Systems and complexity thinking is more than a tool, it is - in a sense - a way of being, namely deeply interested in understanding the highly interconnected and interdependent nature of the issues affecting our life and work. Hence, system and complexity thinking is, contrary to what Haynes and colleagues state in their "summation for the public reader," neither "overwhelming and hard [nor difficult] to use practically." Such a view is as much misleading as self-defeating.